The Impact of ICT Adoption in Enhancing Teaching and Learning in Primary Schools of Amathole East District, Eastern Cape - Mapisa, Bafundi Zealous; Makena, Bulelwa (Research in Social Sciences and Technology, 2024)
This study examines how information and communication technology (ICT) impacts the schooling environment within the primary sector in South Africa's Eastern Cape Province's Amathole East District. ICT adoption in education can fully modify the ways that instruction and learning are given to students, but it also comes with obstacles, especially in the rural primary schools in the Amathole East District. This research intends to shed light on the current ICT status adoption of Amathole East District's primary schools. Three primary schools were chosen, and three research participants from each school were chosen using the purposive sample technique. Data were gathered through focus groups and in-person interviews. The acquired data were analyzed and presented using a thematic approach. It was revealed as the findings that while teachers were willing to embrace ICTs into teaching and learning and had a good attitude toward technology adoption, they needed the necessary ICT competencies. Furthermore, several challenges and barriers were identified, and these included inadequate ICT infrastructure, a shortage of teacher training in technology integration and a lack of access to ICT tools. The study concludes that teacher training programs be expanded, invest in infrastructure development, and develop a comprehensive ICT policy framework. Taking the research's findings into account, the research offers practical recommendations in enhancing ICT adoption, investing in infrastructure development, expanding teacher development opportunities, to formulating a comprehensive ICT strategy framework so that schools are ready to run virtually in the event of another pandemic related to COVID-19.